Worse Prognosis for Stage IA Lung Cancer Patients with Smoking History and More Severe Chronic Obstructive Pulmonary Disease - Yoshida, Yukihiro (Ann Thorac Cardiovasc Surg, 2015)
Purpose: This retrospective study examined whether the severity of chronic obstructive lung disease (COPD) affects surgical outcomes. Methods: The subjects were 243 consecutive patients who underwent lobectomy for clinical stage IA lung cancer from 1999 to 2008 in our hospital. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) grading system was used to classify the severity of COPD in smokers. Results: Among the 149 smokers, 62 were diagnosed with COPD (25 as GOLD 1, 33 as GOLD 2, and 4 as GOLD 3). In univariate analysis, postoperative pulmonary complications were associated with male sex and more severe COPD. The frequencies were 17.1% in non-COPD, 24.0% in GOLD 1-COPD, and 46.0% in GOLD 2/3-COPD smokers (p = 0.0006). In univariate analysis, older age, smoking history, higher smoking pack-years and more severe COPD were associated with poor relapse-free survival. Relapse-free survival at five years was 80.7%, 66.9%, and 61.3% in non-COPD, GOLD 1-COPD, and GOLD 2/3-COPD smokers, respectively (p = 0.0005). Multivariate analyses showed that only GOLD 2/3-COPD was associated with postoperative pulmonary complications and relapse-free survival. Inhaled bronchodilators were prescribed preoperatively to 24.3% of the GOLD 2/3-COPD group. Conclusion: Smokers with GOLD 2/3-COPD are at high risk for pulmonary complications and have an unfavorable long-term prognosis.